2010
DOI: 10.1152/ajprenal.00690.2009
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin increases expression of UT-A1, UT-A3, and ER chaperone GRP78 in the renal medulla of mice with a urinary concentrating defect

Abstract: Activation of V2 receptors (V2R) during antidiuresis increases the permeability of the inner medullary collecting duct to urea and water. Extracellular osmolality is elevated as the concentrating capacity of the kidney increases. Osmolality is known to contribute to the regulation of collecting duct water (aquaporin-2; AQP2) and urea transporter (UT-A1, UT-A3) regulation. AQP1KO mice are a concentrating mechanism knockout, a defect attributed to the loss of high interstitial osmolality. A V2R-specific agonist,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
17
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 37 publications
4
17
1
Order By: Relevance
“…Neither PERK nor ATF4 was activated by urea stress in our study. In vivo, we reported that ATF4 expression increases in the renal medulla of water-restricted mice (3) and in the renal medulla of dDAVP-infused, AQP1-null mice (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither PERK nor ATF4 was activated by urea stress in our study. In vivo, we reported that ATF4 expression increases in the renal medulla of water-restricted mice (3) and in the renal medulla of dDAVP-infused, AQP1-null mice (5).…”
Section: Discussionmentioning
confidence: 99%
“…In a concentrating defect mouse model, we identified a potential role for urea in increasing the endoplasmic reticulum (ER) stress pathway genes glucose response protein 78 (GRP78) and ATF3 and ATF4 in renal collecting ducts (5). The aim of the current study was to determine whether high urea stress directly activated these stress response genes via the eIF2␣ phosphorylation pathway and we addressed this using a renal medullary cell line.…”
mentioning
confidence: 99%
“…In the IMCD, urea is reabsorbed by UT-A1 and UT-A3 from the forming urine, in which urea is concentrated after the reabsorption of water, NaCl, and other useful substances. The urea reabsorption by UT-A1 and UT-A3 is regulated by vasopressin and other factors via PKA- and PKC-mediated pathways (15,32,65,100,123). This urea reabsorption is essential to maintain high urea concentration in the inner medullary interstitium and to set up the intrarenal osmotic gradient between the cortex and the inner medulla.…”
Section: Urea Retention In the Kidney: Urea Transportermentioning
confidence: 99%
“…In mammals, it is well known that vasopressin controls the mRNA expression of UTs and the apical accumulation of UT-A1 via V2-type vasopressin receptor (12,14,15,64). In the houndshark, secretion of vasotocin, a nonmammalian ortholog of vasopressin, is enhanced in concentrated SW, whereas it is decreased in lowsalinity conditions (53).…”
Section: Urea Retention In the Kidney: Urea Transportermentioning
confidence: 99%
“…In response to a reduction in plasma volume and an increase in the plasma osmolality, vasopressin is released from the posterior pituitary and causes an increased urea concentration in the papillary tip, which contributes to the efficiency of the urinary concentrating mechanism (2,21).…”
mentioning
confidence: 99%